Information Security and Assurance International Conference, ISA 2011, Brno, Czech Republic, August 15-17, 2011. Proceedings - Kim, Tai-hoon.; Adeli, Hojjat; Robles, Rosslin John.; Balitanas, Maricel; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the proceedings of the International Conference on Information Security and Assurance, held in Brno, Czech Republic in August 2011.
Keywords: Computer science; Computer network architectures; Computer Communication Networks; Computer system performance; Data structures (Computer science).; Data encryption (Computer science).; Coding theory; Computer Science; Computer Communication Networks; Computer Systems Organization and Communication Networks; Data Structures, Cryptology and Information Theory; Data Encryption; System Performance and Evaluation; Coding and Information Theory